Organizational characteristics of European pediatric onco-critical care: An international cross-sectional survey - Nielsen, Jeppe S. A.; Agbeko, Rachel; Bate, Jessica; Jordan, Iolanda; Dohna-Schwake, Christian; Potratz, Jenny; Moscatelli, Andrea; Bottari, Gabriella; Pappachan, John; Witt, Volker; Crazzolara, Roman; Amigoni, Angela; et al. (Frontiers in Pediatrics, 2022)
Background: Intensified treatment protocols have improved survival of pediatric oncology patients. However, these treatment protocols are associated with increased treatment-related morbidity requiring admission to pediatric intensive care unit (PICU). We aimed to describe the organizational characteristics and processes of care for this patient group across PICUs in Europe. Methods: A web-based survey was sent to PICU directors or representative physicians between February and June 2021. Results: Responses were obtained from 77 PICUs of 12 European countries. Organizational characteristics were similar across the different countries of Europe. The median number of PICU beds was 12 (IQR 8-16). The majority of the PICUs was staffed by pediatric intensivists and had a 24/7 intensivist coverage. Most PICUs had a nurse-to-patient ratio of 1:1 or 1:2. The median numbers of yearly planned and unplanned PICU admissions of pediatric cancer patients were 20 (IQR 10-45) and 10 (IQR 10-30, respectively. Oncology specific practices within PICU were less common in participating centres. This included implementation of oncology protocols in PICU (30%), daily rounds of PICU physicians on the wards (13%), joint mortality and morbidity meetings or complex patients’ discussions (30% and 40%, respectively) and participation of parents during clinical rounds (40%). Conclusion: Our survey provides an overview on the delivery of critical care for oncology patients in PICU across European countries. Multidisciplinary care for these vulnerable and challenging patients remains complex and challenging. Future studies need to determine the effects of differences in PICU organization and processes of care on patients’ outcome.